Effect of materials and manufacturing on the bending stiffness of vaulting poles - Davis, C. L.; Kukureka, S. N. (Physics Education, 2012)
The increase in the world record height achieved in pole vaulting can be related to the improved ability of the athletes, in terms of their fitness and technique, and to the change in materials used to construct the pole. For example in 1960 there was a change in vaulting pole construction from bamboo to glass fibre reinforced polymer (GFRP) composites. The lighter GFRP pole enabled the athletes to have a faster run-up, resulting in a greater take-off speed, giving them more kinetic energy to convert into potential energy and hence height. GFRP poles also have a much higher failure stress than bamboo, so the poles were engineered to bend under the load of the athlete, thereby storing elastic strain energy that can be released as the pole straightens, resulting in greater energy efficiency. The bending also allowed athletes to change their vaulting technique from a style that involved the body remaining almost upright during the vault to one where the athlete goes over the bar with their feet upwards. Modern vaulting poles can be made from GFRP and/or carbon fibre reinforced polymer (CFRP) composites. The addition of carbon fibres maintains the mechanical properties of the pole, but allows a reduction in the weight. The number and arrangement of the fibres determines the mechanical properties, in particular the bending stiffness. Vaulting poles are also designed for an individual athlete to take into account each athlete's ability and physical characteristics. The poles are rated by 'weight' to allow athletes to select an appropriate pole for their ability. This paper will review the development of vaulting poles and the requirements to maximize performance. The properties (bending stiffness and pre-bend) and microstructure (fibre volume fraction and lay-up) of typical vaulting poles will be discussed.